Telehealth delivery of physical therapist-led interventions for persons with chronic low back pain in underserved communities: lessons from pragmatic clinical trials - Fritz, Julie M.; Ford, Isaac; George, Steven Z.; Vinci de Vanegas, Laura; Cope, Tyler; Burke, Colleen A.; Goode, Adam P. (Frontiers in Pain Research, 2024)
In this perspective, we present our experience developing and conducting two pragmatic clinical trials investigating physical therapist-led telehealth strategies for persons with chronic low back pain. Both trials, the BeatPain Utah and AIM-Back trials, are part of pragmatic clinical trial collaboratories and are being conducted with persons from communities that experience pain management disparities. Practice guidelines recommend nonpharmacologic care, and advise against opioid therapy, for the primary care management of persons with chronic low back pain. Gaps between these recommendations and actual practice patterns are pervasive, particularly for persons from racial or ethnic minoritized communities, those with fewer economic resources, and those living in rural areas including Veterans. Access barriers to evidence-based nonpharmacologic care, which is often provided by physical therapists, have contributed to these evidence-practice gaps. Telehealth delivery has created new opportunities to overcome access barriers for nonpharmacologic pain care. As a relatively new delivery mode however, telehealth delivery of physical therapy comes with additional challenges related to technology, intervention adaptations and cultural competence. The purpose of this article is to describe the challenges encountered when implementing telehealth physical therapy programs for persons with chronic low back pain in historically underserved communities. We also discuss strategies developed to overcome barriers in an effort to improve access to telehealth physical therapy and reduce pain management disparities. Inclusion of diverse and under-represented communities in pragmatic clinical trials is a critical consideration for improving disparities, but the unique circumstances present in these communities must be considered when developing implementation strategies.